To Legalize or Not to Legalize? Collective countermeasures in international law - Juhlin-Dannfelt,Roya (2025)
This thesis has examined the right of a non-injured state to take collective countermeasures under international state responsibility law. The concept of collective countermeasures refers to countermeasures that are taken by non-injured states (in the sense of Article 42 ARSIWA) in response to breaches of obligations erga omnes (partes), otherwise referred to as communitarian norms. Such obligations are owed either to the international community as a whole (erga omnes) or to a group of states (erga omnes partes), and protect collective interests. However, the issue of collective countermeasures causes great controversy, as both states and scholars are divided with regards to whether such a right can be said to exist under general international law. An abundance of arguments has been made both in support of and opposed to the recognition of a right to take collective countermeasures. In spite of the polarized discussions on collective countermeasures, state practice indicates that more states are willing to take action by way of collective countermeasures in response to breaches of communitarian norms. This is seen clearly in the ongoing conflict between Russia and Ukraine, which has brought the question of the legality of collective countermeasures back to the table. Through the employment of the legal doctrinal method, re-examination of state practice, however, leads to the conclusion that no customary rule that permits recourse to collective countermeasures exists under international law today, even though the winds seem to be blowing in that direction. This, in turn, begs the question of whether collective countermeasures should be recognized in international law. An analysis of the arguments that have been presented both for and against the recognition of a right to take collective countermeasures demonstrates that, whilst arguments against collective countermeasures cannot be completely discarded, the arguments in support of such a right are more persuasive and bear greater weight. International state responsibility law would therefore greatly benefit from the recognition of collective countermeasures as a tool to enforce communitarian norms in what is otherwise a rather limited toolbox, in order to allow non-injured states a peaceful, yet effective means to respond in the face of breaches of communitarian norms.
Keywords: public international law; collective countermeasures